Microevolutionary dynamics show tropical valleys are deeper for montane birds of the Atlantic Forest - Gregory Thom (Nature Portfolio, 2021)
There are many hypotheses for why the tropics are more biodiverse than higher latitudes. Phylogenomic analyses of 21 montane birds finds that tropical birds disperse less and have more genetically structured populations than their counterparts at higher latitudes, possibly due to a larger elevational climate gradient in the tropics